Positive temperature coefficient material based on silicone rubber/ paraffin/ graphite/ carbon nanotubes for wearable thermal management devices - Hao, Jian-Min; Yang, Yin-Fa; Shen, Yi-Tao; Zhou, Rui; Zhang, Wei; Chen, Hua; Cheng, Wen-Long (Chemical engineering journal (Lausanne, Switzerland : 1996), 2024)
•PTC material with adaptive temperature control performance were prepared.•The material exhibited better flexibility and bending stability.•The material possessed better thermal stability, withstanding temperatures from −20 °C to 120 °C.•The material provides thermal comfort in cold environments without control equipment. PTC materials provide substantial advantages such as adaptive temperature control performance and excellent safety. However, their use in wearable devices has been limited due to the essential requirements for flexibility and stability. This study prepared a new type of flexible PTC material, with a PTC intensity of 6.3 and a resistivity of only 400 Ω·cm in the low-temperature region. The flexibility of the material is evidenced by its 2 mm bending diameter and its ability to maintain structural integrity even after 100 bends. Furthermore, experimental evidence proves that PTC material has excellent thermal stability and can withstand extreme temperatures ranging from −20 °C to 120 °C. In the thermal control experiment, the PTC material maintains a temperature of approximately 25 °C to accommodate the requirements of the human body in a cold environment. When compared to the conventional PI heating sheet, the newly prepared PTC material exhibits advantages such as rapid response, adaptive temperature control performance, and safety. Consequently, it presents a broad application prospect in the field of wearable heating devices.